Norovirus - Mózsik, Gyula (IntechOpen, 2021)
This book provides an overview of norovirus, a viral infection that adversely affects the gastrointestinal system. Unfortunately, there is no specific treatment available for this illness. As such, the World Health Organization (WHO) has identified norovirus as a priority disease for vaccine development. Chapters in this edited volume cover such topics as examination methods and genome mechanisms of norovirus, and clinical and pharmaceutical developments in managing this illness.